Ectopic expression of OPKN1 gene in N. benthamiana alter flower size and delay flowering time - Mohd Waznul Adly, M.Z.; Zuraida, A.B.; Wee, C.Y.; Alizah, Z.; Norliza, A.B.; Che Radziah, C.M.Z. (Penerbit Universiti Kebangsaan Malaysia, 2015)
Oil Palm Knotted-like 1(OPKN1) gene is a type of homeobox gene that was previously isolated from cDNA library of oil palm’s suspension cell culture. Based on semi-quantitative RT-PCR, northern blotting and in situ hybridization analysis, the OPKN1 gene is active in flower meristem suggesting its involvement in flowering phase. Semi-quantitative RT-PCR analysis indicated that OPKN1 gene is active in both male and female flowers and also in abnormal flower suggesting its role in flower morphogenesis process. To further validate the function of this gene, the overexpression transformation vector of OPKN1 gene driven by CaMV 35S constitutive promoter was constructed. The constructed vector was transformed into plant model systems Nicotiana benthamiana via Agrobacterium tumefaciens. Four transgenics lines of N. benthamiana were successfully obtained and analysis of quantitative Real-Time PCR shows that OPKN1 gene was highly overexpressed in all transgenic lines. Overexpression of OPKN1 gene in N. benthamiana transformant has caused reduction in N. benthamiana’s flower size and flowering time was also observed to be delayed. Based on this finding, it was suggested that OPKN1 may be involved in flower development and morphogenesis process.